Role of Herbal Medication in Tobacco Cessation Treatment: A Systematic Review and Meta-analysis - Ruchi Mitra; Arpita Rai; Ansul Kumar; Jeewan Kumar Mitra (Addiction and Health, 2023)
Background: Literature reports randomized trials have examined herbal drugs and other smoking cessation therapies such as aromatherapy acupuncture but no comprehensive overview of the overall results has been provided. The present systematic review and meta-analysis aimed to describe the overall effectiveness and safety of herbal medicines. Methods: This study was conducted from December 2020 to April 2021 by searching seven databases. Herbal drugs have been shown to help people quit smoking in randomized controlled studies. Two teams of researchers independently extracted the data. Findings: A total of 12 trials with 762 smokers were included in this study. The heterogeneity I2 was 43.6% with P=0.03 (Cochrane Q test) and χ2=15.77. The overall odds ratio (OR) at 95% confidence interval (CI) was 0.91 (0.68- 1.20) which shows a protective factor of herbal preparations and very low heterogeneity. The herbal treatments such as Vernonia cinerea, St. John’s Wort, and lavender essential oil were significantly related to a higher continuous abstinence rate (CAR) compared to the controls with risk ratio (RR): 2.13 (0.57-4.61) at week 8; RR: 2.72 (0.77-5.3) at week 12; and RR: 2.77 (0.37-1.13) at week 24. A 7-day point abstinence rate (PAR) at week 8 was RR: 1.24 (0.81-6.34) with 95% CI; RR: 2.09 (0.93-8.29) at week 12, and RR: 2.11 (0.3-3.08) at week 24.Black pepper and lime were better in craving reduction than the placebo group. This study found no significant difference between the treatment and control groups in adverse effects, despite some minor side effects with herbal drugs. Conclusion: The results of this study showed herbal treatments have the potential to help smokers quit the habit. Further well designed trials comparing standardized herbal medicines with conventional therapy and placebo are recommended to reinforce this data.